Lecturers’ Perceptions About the Implementation of Functions of Head of Higher Education - Walef, Sri Mures; Nikmatulaili, Nikmatulaili; Rusdinal, Rusdinal; Gistituati, Nurhizrah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The purpose of this study is to describe the lecturers’ perceptions of the implementation of the functions of the chairman of STKIP Abdi Pendidikan in terms of administrators and managers. This type of research is quantitative using descriptive methods. The research population is also the research sample, which consists of 36 lecturers and educational staff. The research instrument is a questionnaire that has been tested for its validity and reliability. The results showed that the lecturer’s perception of the implementation of the chairperson’s function was in the good category with an average score of 3.87. The lecturer’s perception of the implementation of the chairman’s manager function is in the good category with an average score of 3.83. So, the lecturer’s perception of the implementation of the administrator and manager functions of the head of STKIP YAP is in the good category with an average of 3.85.